Serum Neutralization of SARS-CoV-2 Omicron BA.1 and BA.2 after BNT162b2 Booster Vaccination - Rune M. Pedersen (Emerging Infectious Diseases, 2022)
The SARS-CoV-2 Omicron variant BA.2 sublineage is rapidly replacing earlier Omicron lineages, suggesting BA.2 has increased vaccine evasion properties. We measured neutralization titers of authentic BA.1 and BA.2 isolates in serum samples from persons who received the BNT162b2 booster vaccine. All samples neutralized BA.1 and BA.2 at equal median values.